#### Thank you for registering.

One of our academic counsellors will contact you within 1 working day.

Click to Chat

1800-1023-196

+91-120-4616500

CART 0

• 0
MY CART (5)

Use Coupon: CART20 and get 20% off on all online Study Material

ITEM
DETAILS
MRP
DISCOUNT
FINAL PRICE
Total Price: Rs.

There are no items in this cart.
Continue Shopping

# A (g) + B(g) = C(g) + D(g) Above equilibrium is established by taking A and B in a closed container. Initial concentration of A is twice the initial concentration of B. At equilibrium concentration of B and C are equal. Then find the equilibrium constant for the reaction, C(g) + D(g) = A(g) + B(g)

8 years ago

A (g) + B(g)  =  C(g) + D(g)

t=0         2a        a            0         0

t=t       2a - x     a - x       x         x

At equilibrium concentration of B and C are equal.

a - x   =    x

a = 2x

x = a/2

Now,

at t=t 3a/2      a/2         a/2      a/2

K = [A] [B]/[C] [D]

K = [3a/2] [a/2]/ [a/2]2

K = 3a^2/4/a^2/4

K = 3

is te ansr.

Approve! plz